Translation strategies for video game literature : a case study of the authorized novelization for Assassin’s Creed - Yu, Tong (Nanyang Technological University, 2020)
Video game industry has seen massive growth in the last two decades. With the booming prosperity, many attempts have been made to monetize the success, including through the novelization of games and production of other derivative literature works. However, this incited a new issue. Game literature is highly aligned with the original video game in content, hence, most of the potential audience would be video game players. Given the fast-changing and highly-domesticated nature of video game and video game localization, an issue has arisen. Should the strategies applied in translation of canonized literature be used for game literature? Or should other alternatives be considered? To increase the monetization possibilities of such game-literature works, the pertinent question is how we “convert” game players into readers. By conducting linguistic and theoretic analysis of the official novelization of Assassin’s Creed: Odyssey (by Gordon Doherty) and its authorized Chinese-language translation (by A Zei and Huang Peiyuan), the present research proposes a set of new strategies more focused on the domestication and level of communicativeness of the translated text. In order to gather quantitative data regarding the practicality and effects of the new strategy, a survey was carried out via questionnaires on 13 video game enthusiasts and another 10 translation/literature professionals. The volunteers were prompted to rate two unmarked translations of the pertinent text. One of the two is the authorized Chinese translation, the other was generated using the proposed set of new strategies. According to survey results, this set of strategies significantly increased the readability and smoothness of the target text, hence generating a reading experience closer to that of playing a video game, while potentially increasing the conversion rate between players and readers.